PRODUKSI BIOETANOL DARI NIRA AREN MENGGUNAKAN ENERGI GEOTHERMAL - Tangkuman, Herling D.; Rorong, Johnly A.; Pandara, Dolfie; Tamuntuan, Gerald (CHEMISTRY PROGRESS, 2010)
The results obtained as follows: 400 L didestilasi fermented sap fractionation and at a temperature of 82 Â°Cdestilat began to drip. At the end of the distillation process, is obtained destilat as much as 86 L 35% ethanol.Then the results obtained diredestilasi returned 36 L 78% ethanol, then the results added lime and then backdidestilasi results obtained is 28 L 96% ethanol. The next Prosess purification with the addition later inanhidrous compounds using zeolite filtration to obtain 99% ethanol. From purified bioethanol chromatogram inFigure 5, shows that the peak that appears only one (single) at the retention time of 3.03 minutes with a 99.5%level. Chromatogram of bioethanol palm juice samples in Figure 5 shows that the peak with retention time of3.02 minutes is the most dominant peak levels of 96.77%. Peak with retention time of 3.02 minutes for thesample destilat similar retention time for bioethanol Purified (3.03 minutes). This shows that the largestcomponent in the sample is ethanol destilat. Peak with retention time 2.45 minutes on the chromatogram image5 (sample bioethanol) with levels of 2.174%, the sample is expected ester compounds. This is supported by theresults of the determination of sample density, higher destilat (0.8288 g/mL) from the weight of pure ethanol(0.79 g/mL). While the results of an infrared spectrophotometer for pure ethanol and the sample obtained asfollows; Based on the spectrum of pure ethanol in Figure 6, shows the existence of prolonged vibration of theOH absorption at 3232.99 cm-1. In the absorption region 2968.71 cm-1 and 2901.11 cm-1 indicate a prolongedvibration of CH of CH2 and CH3. In the absorption region 1450.46 cm-1 showed a prolonged vibration of CH2.Prolonged vibration of the CH3 region is also shown on the uptake 1383.09 cm-1 and 1332.93 cm-1 absorption inthe region 1045.51 cm-1 indicate a prolonged vibration of CO of alcohol.